Uji Kualitas Massa Batuan Berdasarkan Metode Rock Mass Rating Desa Longalo, Kabupaten Bone Bolango - Moh. Raihan Anwar; Muh. Kasim; Ayub Pratama Aris (Geosfera: Jurnal Penelitian Geografi, 2025)
This study was conducted in Longalo Village to determine the rock mass quality using the Rock Mass Rating (RMR) method. The analysis was carried out on five field observation segments. The lithology of the study area consists of granitic rocks, most of which have undergone deformation, especially along the slope areas. Geological factors such as the degree of weathering and structural conditions influence the rock mass assessment. The analysis results show that the RMR values range from 48 to 56, which are classified as Class III or fair-quality rock. Based on this classification, the rock mass conditions in the study area are generally fairly stable but are still influenced by structural features and weathering.